Central nociceptive sensitization vs. spinal cord training: opposing forms of plasticity that dictate function after complete spinal cord injury - Ferguson, Adam R.; Huie, J. Russell; Crown, Eric D.; Grau, James W. (Frontiers in Physiology, 2012)
The spinal cord demonstrates several forms of plasticity that resemble brain-dependent learning and memory. Among the most studied form of spinal plasticity is spinal memory for noxious (nociceptive) stimulation. Numerous papers have described central pain as a spinally-stored memory that enhances future responses to cutaneous stimulation. This phenomenon, known as central sensitization, has broad relevance to a range of pathological conditions. Work from the spinal cord injury (SCI) field indicates that the lumbar spinal cord demonstrates several other forms of plasticity, including formal learning and memory. After complete thoracic SCI, the lumbar spinal cord can be trained by delivering stimulation to the hindleg when the leg is extended. In the presence of this response-contingent stimulation the spinal cord rapidly learns to hold the leg in a flexed position, a centrally mediated effect that meets the formal criteria for instrumental (response-outcome) learning. Instrumental flexion training produces a central change in spinal plasticity that enables future spinal learning on both the ipsilateral and contralateral leg. However, if stimulation is given in a response-independent manner, the spinal cord develops central maladaptive plasticity that undermines future spinal learning on both legs. The present paper tests for interactions between spinal cord training and central nociceptive sensitization after complete spinal cord transection. We found that spinal training alters future central sensitization by intradermal formalin (24 h post-training). Conversely intradermal formalin impaired future spinal learning (24 h post-injection). Because the NMDA receptor has been implicated in formalin-induced central sensitization, we tested whether pretreatment with NMDA affects spinal learning. We found intrathecal NMDA impaired learning in a dose-dependent fashion, and that this effect endures for at least 24h. These data provide strong evidence for an opposing relatio